Vascular pedicled iliac bone grafting is effective in patients with an early stage of femoral head avascular necrosis - ELMALI, NURZAT; Elmali, NURZAT; ERTEM, KADİR; KARAKAPLAN, MUSTAFA; PEPELE, Demet; Daggez, Cihat; Topgul, Haldun (My University, 2014)
Objectives: This study aims to evaluate clinical and radiological findings of a series of patients with avascular necrosis of the femur head (ANFH) treated by core decompression and vascular pedicled iliac crest grafting.